(untitled) (Fiep Bulletin - online, 2012)
Abstract: premature birth is responsible for a large number of hospitalizations in Neonatal Intensive therapy Units (UTINs), since these newborns are at risk of life, requiring greater attention to health. In this context, the health team that plays in the NICU must be trained to respond to the premature and its peculiarities, with a view to promoting quality of life of this yearling, offering individualized care and directed to integral development. Among the strategies for the promotion of a great environment for growth and development has been the care development status. Thus, the goal of this study is to describe if nurses develop actions directed to the careful development status in UTINs, especially as regards reduction of luminosity, noise and handling. It is a descriptive and exploratory study involving nurses who work in public UTINs of the city of Natal, State of Rio Grande do Norte in the year 2011. The sample was intentional and for convenience. Data collection took place after contact with nurses who will be invited to answer a questionnaire about their knowledge related to developmental care and which actions are carried out in accordance with those interventions proposed by Newborn Individualized Developmental Care and Assessment Program (NIDCAP) NIDCAP. The data revealed that the nurses should pay attention to situations of environmental stress, understood in those related to equipment, as well as those restricted to multiprofessional team, driving the creation of healthy environments in case of hospitalization, and with this better recovery. Thus, one can infer that keep the ICU environment with devices that mitigate or eliminate the noise is characterised in a measure of caution, that must also be perceived by the nurses.